+0  
 
0
289
2
avatar+30 

i needs help

 

what is the distance formula?

TheBestAquamarine  Aug 3, 2017

Best Answer 

 #2
avatar+7324 
+3

Let's look at the points  (4, 5)  and  (6, 2)  for example.

We can make a right triangle out of these points like this...

 

Notice that side  c  is the distance between the two points.

 

And..we can find the length of side  c  using the Pythagorean theorem, which says..

 

    a2    +     b2     =  c2

                                                       The length of side  a  =  5 - 2  =  3

(5 - 2)2 +     b2     =  c2

                                                       The length of side  b  =  6 - 4  =  2

(5 - 2)2 + (6 - 4)2  =  c2

                                                       Take the positive square root of both sides.

\(\sqrt{(5-2)^2+(6-4)^2}=c\)

 

And this is where the distance formula comes from. It says..

 

\(\text{distance}=\sqrt{(x_1-x_2)^2+(y_1-y_2)^2}\)

 

And, as CPhill noted, the order of subtraction within the parenthesees doesn't matter.

hectictar  Aug 3, 2017
 #1
avatar+90088 
+2

 

Suppose that we have two points (x1, y1)  and (x2, y2)

 

The distance between these is just

 

sqrt [  (  x2 - x1)^2 + ( y2 - y1)^2 ]   ..  actually....the order of subtraction is immaterial...we could subtract (x1 - x2 )  or (y1 - y2) or both in this order

 

Example.....distance between (5,3)  and (8, 2)

 

sqrt [  ( 5 - 8)^2 + (3 - 2)^2 ]   =  sqrt [ (-3)^2 + 1^2 ]  =  sqrt [ 9 + 1 ] =  sqrt (10)  units ≈  3.16 units

 

 

cool cool cool

CPhill  Aug 3, 2017
edited by CPhill  Aug 3, 2017
edited by CPhill  Aug 3, 2017
edited by CPhill  Aug 3, 2017
 #2
avatar+7324 
+3
Best Answer

Let's look at the points  (4, 5)  and  (6, 2)  for example.

We can make a right triangle out of these points like this...

 

Notice that side  c  is the distance between the two points.

 

And..we can find the length of side  c  using the Pythagorean theorem, which says..

 

    a2    +     b2     =  c2

                                                       The length of side  a  =  5 - 2  =  3

(5 - 2)2 +     b2     =  c2

                                                       The length of side  b  =  6 - 4  =  2

(5 - 2)2 + (6 - 4)2  =  c2

                                                       Take the positive square root of both sides.

\(\sqrt{(5-2)^2+(6-4)^2}=c\)

 

And this is where the distance formula comes from. It says..

 

\(\text{distance}=\sqrt{(x_1-x_2)^2+(y_1-y_2)^2}\)

 

And, as CPhill noted, the order of subtraction within the parenthesees doesn't matter.

hectictar  Aug 3, 2017

20 Online Users

avatar
avatar
avatar
avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.